Consciousness, synchronicity and art – implications in creative thinking and direction of the art in relation to the concept of universe and reality in quantum mechanics. Issue 1 (1st March 2017) - Lopreiato, Paola
The concept of simultaneity and contemporaneity is fundamental to and the core of my artistic practice but it also fits perfectly with the theme of my research. Creating multimedia art and installations with the help of new media is one way to best express the concept of non-separation, as evidenced by language itself. In Italian the word confusione, from the Latin term cunfusionem (mixing, blending), and in English confusion, is often used as a synonym for noise. In English, commotion is a synonym for blare, and it has been derived from the Latin word cum movere, which means moving together. Contemporary art and installation are both staticity and change intermingled in a single place and time. The study of crowd, and the emotion that emerges from the deep immersive experiencing of art, is also strongly linked to another concept developed by Bergson: intuition. By 'intuition', Bergson meant an elementary, indivisible experience of sympathy, through which a person is moved into the inner being of an object and can comprehend what is unique and indefinable in it. I hypothesize the presence and expression of emotion in the collective experience of installation art, and both my creative efforts and theoretical research are aimed at facilitating the audience's understanding or intuition of this emotion in an immersive multisensory environment. Using a range of both technological and classical tools and means of expression in my work, but more generally, artists create a product that can mediate and unfold the complexity of the phenomenological event by rendering it in a new form accessible to all.